CO2 emissions from the private automotive system in the northern border states of Mexico: a monetary valuation exercise - Camarena Gómez, Beatriz Olivia; Hernández Arias, Pablo; Robles Parra, Jesús Martin; Salazar Solano, Vidal; León Balderrama, Jorge Inés (Acta Universitaria, 2022)
The urban and demographic growth presented in recent years by the states of the northern border of Mexico (EFNM) has impacted their respective land mobility systems, their demand for energy resources, and their carbon emissions. In this context, the objective of the study is to analyze the environmental performance of the private urban mobility system (SPMU) in this region, by assessing its carbon emissions into the atmosphere, based on an eco-integrative perspective. The results corroborated the growing trend of the vehicle fleet and the monetary value of emissions, but not a greater demand for energy or an increase in such emissions. It is concluded that the world crisis and the national macroeconomic context determined the environmental performance of the SPMU more than its endogenous factors. It is recommended to reinforce this line of research considering sustainable alternative scenarios and integrating more variables into the analysis scheme.